ANALYSIS OF THE INFLUENCE OF BANK INTERNAL FACTORS AND MACROECONOMIC CONDITIONS ON NON PERFORMING LOAN (NPL) OF COMMERCIAL BANKS IN INDONESIA - Sholiha, Ayu; Mukhlis, Imam (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The purpose of this study is to determine the impact of bank internal factors and macroeconomic conditions on non-performing loans (NPL). The variables used are the capital adequacy ratio (CAR), loan to deposit ratio (LDR), bank size, gross domestic product (GDP), inflation, and the BI rate. The method used is a quantitative method with secondary data in the form of financial statements of 5 banks as research objects. The data analysis technique used is panel data regression, hypothesis testing using the t-test to test the effect of variables partially and the F test to test the effect of variables simultaneously with a significant level of 5%. Based on these results it was concluded that partially the LDR and the BI Rate had a significant effect on NPL. Meanwhile, CAR, bank size, GDP and inflation have no significant effect on NPL. Simultaneously, all independent variables have a significant effect on the level of NPL influence.